Optimizing Hysteresis Parameters Of Magneto-Rheological Fluid Damper Using Particle Swarm Optimization - Mohd Azraai, M. Razman; Priyandoko, Gigih; A. R., Yusoff; M. F. F., Ab Rashid (2014)
Magneto-rheological (MR) fluid has been used in various application as it seen to increase performance from a basic machine into high performance robust machine. A damper that is partnered with MR fluid can increase the operation of vibration suppression in a bigger range compared to a passive shock absorber. MR fluid damper has the property of engaging prediction not just forthcoming behaviour but retracting the preceding measurement. With suitable parameters projected to the hysteresis model, the trajectory for MR fluid damper model can be realize and attain required absorber performance. This study target on implementing Particle Swarm Optimization (PSO) to in searching the optimum parameters value of the hysteresis model for MR fluid damper. Validation by physical experiment and simulation was conducted to enhance the justification of the present model. These performances are measure in force against displacement and force against velocity for the hysteresis model to depict MR fluid damper behaviour. The average marginal error was presented to strengthen the model along with analysis and discussion in deliberating the outcome.